On Rayleigh Quotient Matrices: Theory and Applications (Journal of Computational Mathematics, 2021)
Many authors have studied the Rayleigh quotient and Rayleigh quotient matrix. This paper consists of two parts. First, generalizations of some results on the Rayleigh quotient are proved. Second, we give some applications of these theoretical results.